Pengaruh pemberian dosis pupuk kandang kambing dan pupuk fosfat (p0 terhadap pertumbuhan dan hasil tanaman kacang tunggak (Vigna ungiculata L. Walp): Kacang tunggak, pupuk kandang kambing, pupuk SP 36 - Sherin Dwi Yahmanto; Sumarmi, Sumarmi; Triyono, Kharis (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2023)
This study entitled The Effect of Goat Manure and Phosphate (P) Fertilizer on the Growth and Yield of Cowpea (Vigna unguiculata L. Walp) to determine the effect of fertilization and phosphorus (p) on the fertility of cowpea (Vigna unguiculata L. Walp) (Vigna unguiculata L. .walp). Cowpea (Vigna unguiculata L Walp.) is a plant that is widely cultivated by humans, especially people in rural areas. Young pods and cowpea seeds are often used as vegetables. Cowpeas have many variations in appearance and are also higher in vitamin B1. The research design used was the RAKL model (complete randomized block design) with 2 factors and was repeated 3 times. The use of goat manure (K) as factor 1 consisted of 4 steps, K0 (control), K1 = 90 grams of goat manure, K2 = 120 grams of goat manure, K3 = 150 grams of goat manure. SP 36 fertilizer as factor 2 consisted of 4 levels, namely P0 (control), P1 = SP 36 fertilizer 1.2 grams, P2 = SP 36 fertilizer 2.4 grams, P3 = SP 36 fertilizer 3.6 grams. Data analysis is used to determine the effectiveness of a treatment using data analysis followed by a follow-up test of BNJ at the 5% level. The results of the study concluded that the treatment of goat manure affected the number of leaves, number of pods, fresh fruit weight, dry fruit weight, fruit/tree weight and 100 seed weight with the best ratio of 150g/tree. The SP 36 treatment affected the number of fruits, fresh fruit weight, dry fruit weight, fruit/plant weight and 100 seed weight with the best ratio of 3.6 g/tree